2015
DOI: 10.1212/nxg.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging findings in Parkinson disease associated with the A53E SNCA mutation

Abstract: Objective:To describe the clinical features and brain imaging findings of autosomal dominant Parkinson disease (PD) associated with a recently reported mutation in SNCA.Methods:A Finnish family with PD in 3 successive generations, in accordance with an autosomal dominant inheritance pattern, was identified. We examined 2 available members of the family, the female proband and her daughter (both with early-onset PD), clinically and using dopamine transporter imaging ([123I]FP-CIT SPECT). A possible causative ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…Disease age at onset varied widely among A53E carriers in this Canadian family (aged 25 to 58 years), similar to the published Finnish cases (aged 25 to 62 years) . We previously showed, in C9orf72 ‐related amyotrophic lateral sclerosis and/or frontotemporal dementia that disease age at onset correlated with DNAm age acceleration .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease age at onset varied widely among A53E carriers in this Canadian family (aged 25 to 58 years), similar to the published Finnish cases (aged 25 to 62 years) . We previously showed, in C9orf72 ‐related amyotrophic lateral sclerosis and/or frontotemporal dementia that disease age at onset correlated with DNAm age acceleration .…”
Section: Resultsmentioning
confidence: 99%
“…Missense mutations and multiplications of SNCA , which encodes α‐synuclein, cause autosomal‐dominant parkinsonism . The most recently identified SNCA mutation, c.158C>A; A53E (A53E), has only been described among Finnish families originating from a common founder . Disease phenotypes associated with A53E are variable, even within families; for example, age at onset can vary by 30 years.…”
mentioning
confidence: 99%
“…Five patients were reported in five case reports [46][47][48][49][50] (STN n = 4, GPi n = 1). The motor outcome was favourable for all patients in the short-term but 3/5 patients developed cognitive and/or neuropsychiatric problems a few years after implantation.…”
Section: Sncamentioning
confidence: 99%
“…Consistent with the latter observation, imaging studies have shown evidence of dopaminergic dysfunction in subjects with a number of pathogenic mutations. The A53T and A53E mutations in the alpha‐synuclein gene ( SNCA ) can be associated with early, relatively symmetrical defects in presynaptic dopaminergic function . Additionally, recessive Parkin and PINK1 mutations appear to be mostly associated with symmetrical dopaminergic losses, whereas in carriers of more‐frequent LRRK2 and GBA mutations, the dopaminergic defect is practically indistinguishable from that of sporadic PD .…”
Section: Molecular Imaging Of Pd and Its Progressionmentioning
confidence: 99%
“…The A53T and A53E mutations in the alpha-synuclein gene (SNCA) can be associated with early, relatively symmetrical defects in presynaptic dopaminergic function. 19,20 Additionally, recessive Parkin 21-23 and PINK1 19 mutations appear to be mostly associated with symmetrical dopaminergic losses, whereas in carriers of more-frequent LRRK2 and GBA mutations, the dopaminergic defect is practically indistinguishable from that of sporadic PD. 19,24 In GBA-associated PD, the severity of dopaminergic dysfunction is related to the degree of glucocerebrosidase enzymatic activity reduction induced by the specific GBA mutation: Carriers of mild mutations (e.g., N370S) overlap with PD noncarriers, whereas PD carriers of severe mutations (e.g., L444P) have a similar phenotype to dementia with Lewy bodies.…”
Section: S T R a F E L L A E T A Lmentioning
confidence: 99%